2014
DOI: 10.4236/ajps.2014.513225
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Water Use Effeciency of Forage <i>Sorghum</i> as Affected by Npk Fertilizer and Deficit Irrigation

Abstract: Drought stress (DS) is an important limiting factor for crop growth and production in some regions of the world. Limitation in water availability precludes optimal irrigation in some production regions. Therefore, investigations on the interaction of other factors to mitigate the DS to varying degree are important. Two field experiments were conducted in the experimental farm of the National Research Centre, Shalakan, Kalubia Governorate, Egypt, during 2004 and 2005 summer seasons to evaluate the interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
(24 reference statements)
1
16
0
Order By: Relevance
“…Interestingly, the diameter of internodes elongating under water deficit was not significantly affected by drought and thus did not contribute to the reduction of stem biomass ( Table 2 and Figure 4 ). Ottman et al (2001) , Almodares et al (2013) , Hussein and Alva (2014) , and Fracasso et al (2016) attributed the reduction of stem biomass by drought to a reduction of plant height but did not relate this response to internode size and number. Although some reports showed that biomass production is more determined by stem height than diameter, particularly across genetic variation ( George-Jaeggli et al, 2011 ; Salas Fernandez et al, 2015 ), the present study is not in line with some other studies: Almodares et al (2013) reported for two genotypes that stem diameter was reduced proportionally to drought intensity and contributed to the reduction of stem biomass.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the diameter of internodes elongating under water deficit was not significantly affected by drought and thus did not contribute to the reduction of stem biomass ( Table 2 and Figure 4 ). Ottman et al (2001) , Almodares et al (2013) , Hussein and Alva (2014) , and Fracasso et al (2016) attributed the reduction of stem biomass by drought to a reduction of plant height but did not relate this response to internode size and number. Although some reports showed that biomass production is more determined by stem height than diameter, particularly across genetic variation ( George-Jaeggli et al, 2011 ; Salas Fernandez et al, 2015 ), the present study is not in line with some other studies: Almodares et al (2013) reported for two genotypes that stem diameter was reduced proportionally to drought intensity and contributed to the reduction of stem biomass.…”
Section: Discussionmentioning
confidence: 98%
“…Abou-Amer & Kewan (2014) stated that fodder yield was increased significantly by increasing N and P fertilizer levels. Also, Hussein & Alva (2014) reported that the increased rates of N, P, K increased the plant growth and biomass. Sorghum hybrids produce more biomass as compared with their parents (Sahoo, 2010).…”
Section: Biological Yield (T Ha -1 )mentioning
confidence: 99%
“…It was also noted that soil aluminum caused significant stress for sorghum. The amounts of N, P, and K in soils are critical to determine fertilizer doses incorporated to soils to increase the yields of sorghum as well as other crops [30,31]. Small amount of nutrients, particularly Zn, Fe, and Mn applied by foliar spraying significantly promote the yield of crops [32].…”
Section: Introductionmentioning
confidence: 99%